2014
DOI: 10.7554/elife.02076
|View full text |Cite
|
Sign up to set email alerts
|

Gating of neural error signals during motor learning

Abstract: Cerebellar climbing fiber activity encodes performance errors during many motor learning tasks, but the role of these error signals in learning has been controversial. We compared two motor learning paradigms that elicited equally robust putative error signals in the same climbing fibers: learned increases and decreases in the gain of the vestibulo-ocular reflex (VOR). During VOR-increase training, climbing fiber activity on one trial predicted changes in cerebellar output on the next trial, and optogenetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 109 publications
(298 reference statements)
7
91
0
Order By: Relevance
“…It was recently reported that a single spike in a climbing fiber in vivo can induce plasticity (Kimpo et al, 2014;Medina and Lisberger, 2008;Yang and Lisberger, 2010). We tested whether there was short-term plasticity at the PF-to-PC synapses in response to a single pairing of parallel fiber and climbing fiber activation (see also Brenowitz and Regehr, 2005), which could support the single-trial plasticity observed in vivo during motor learning.…”
Section: Single-trial Short-term Associative Plasticity In the Floccmentioning
confidence: 91%
See 3 more Smart Citations
“…It was recently reported that a single spike in a climbing fiber in vivo can induce plasticity (Kimpo et al, 2014;Medina and Lisberger, 2008;Yang and Lisberger, 2010). We tested whether there was short-term plasticity at the PF-to-PC synapses in response to a single pairing of parallel fiber and climbing fiber activation (see also Brenowitz and Regehr, 2005), which could support the single-trial plasticity observed in vivo during motor learning.…”
Section: Single-trial Short-term Associative Plasticity In the Floccmentioning
confidence: 91%
“…Long-term associative plasticity in the flocculus in vitro: Temporal requirements matched to behavioral function Our finding that coincident parallel fiber and climbing fiber stimulation failed to induce LTD in the flocculus was surprising, given the multiple lines of evidence for a role of climbing fiber-triggered LTD in flocculus-dependent learning (e.g., Boyden et al, 2006;Hansel et al, 2006;Ito, 2001;Kimpo et al, 2014;Medina and Lisberger, 2008). However, in vivo, the activation of climbing fibers by performance errors would be delayed relative to the parallel fiber activity that caused the error, rather than coincident.…”
Section: Heterogeneity In the Rules For Long-term Plasticity At Cerebmentioning
confidence: 99%
See 2 more Smart Citations
“…The VOR presumably evolved to stabilize large-field, rather than foveal, images, because it is a phylogenetically primitive oculomotor behavior that functions in species without a fovea. Accordingly, VOR learning can be induced by pairing passive head motion with coherent, large-field image motion (Ito et al, 1974;Miles and Fuller, 1974;Gonshor and Jones, 1976;Robinson, 1976;Watanabe, 1984). In primates, however, the oculomotor system has evolved the ability to track a small object of interest, using smooth pursuit eye movements.…”
Section: Introductionmentioning
confidence: 99%